Investigate Driving Repurchase Factors in Omnichannel Services - Edwin Sanjaya (Soegijapranata Catholic University, 2020)
Nowadays, lots of companies compete to win their consumers' hearts so they become loyal to the company. Innovation is always done by companies to provide the best service. The omnichannel concept is one of innovation that suitable for this era. Omnichannel is when company can provide seamless experience for their consumer. But, sometimes the reality is not the same as expected before. Even though companies have implemented these omnichannel systems, sometimes they still fail to engage more customers. Therefore, the purpose of this study was to determining factors that influence repurchase intention so that later it can help researchers and also from the managerial side to using existing factors to manage their strategies. The method used in this study was carried out through three steps, namely planning, action, and reporting. Literature search in this study used Google Scholar as a database. Researcher searched articles using keyword repurchase intention, with condition that the articles are complete. This study received ten articles that were investigated by researchers to obtain several influential factors. The finding of this study is there are eighteen factors influence repurchase intention, but further research needs to be done because of different situations, and conditions can produce different results.